Pressure enabled drug delivery (PEDD) of nelitolimod increased therapeutic delivery, reduced immunosuppression, and improved efficacy in porcine and murine liver tumor models - Cournoyer, Lauren; Liu, Yujia; Jaroch, David B.; Hullinger, Tom G.; Cox, Bryan F.; Katz, Steven C.; LaPorte, Jason; Layman, Ilan B.; Ballarin, Alizee; Ghosh, Chandra C.; Guha, Prajna (Frontiers in oncology, 2025)
Direct tumoral needle injection of nelitolimod, also known as SD-101, has been evaluated in patients with superficial malignancies, including cutaneous melanoma, with encouraging outcomes. Direct intra-tumoral injections may not be suitable for primary and metastatic liver tumors due to the number and size of the lesions, and the location of target immune cells in the peri-tumoral parenchyma. Conventional systemic infusion may be inadequate due to high intra-tumoral pressure and distribution of the therapeutic in large quantities to non-target tissue. Previous clinical and preclinical reports suggest that nelitolimod favorably reprograms the tumor microenvironment to limit myeloid-induced immunosuppression and promote anti-tumor immunity. The present study was undertaken to further explore the contribution of pressure-enabled drug delivery (PEDD) to the immune and clinical effects of nelitolimod in intrahepatic malignancy. Transgenic pigs (oncopigs) with liver tumors received intra-arterial infusions of fluorescently labeled ODN2395 or nelitolimod either via PEDD with a specialized infusion device or with conventional microcatheter delivery in both lobar and selective infusions. Near-infrared imaging assessed tissue distribution. The murine liver metastasis (LM) model was developed by injecting MC38-Luc cells into the C57/BL6 spleen and treating with fluorescently labeled nelitolimod (30µg/mouse). Tumor burden was monitored by an imaging system, serum cytokine levels were analyzed by Luminex, and blood chemistry was measured. Liver CD45+ cells were analyzed by flow cytometry to evaluate the tumor microenvironment. Our results demonstrate that PEDD enhanced the intravascular infusion of nelitolimod into the liver tumor and peri-tumoral tissue. PEDD resulted in a significant increase in distribution and signal intensity (a surrogate for concentration) in target tissue compared to needle injection or a standard catheter in the oncopig model. PEDD was also modeled in the murine setting with a pressure-controlled infusion system. Single treatment of nelitolimod via PEDD, significantly reduced tumor progression as compared to systemic administration. PEDD of nelitolimod significantly reduced immunosuppressive MDSCs and an increase in cytotoxic CD8 + T cells within the LM. In conclusion, use of PEDD enhanced targeted therapeutic delivery in swine liver tumors and reduced tumor progression by promoting anti-tumor immunity in murine LM in association with suppressive myeloid cell elimination.